(untitled) (El Hilo de la Fabula, 2018)
The work briefly through the poetics of E.A. Vigo emphasizing the creative evolution, from its first things towards the achievable utopias and its drifts in the formation of an art expanded in the city of La Plata. Their artistic proposals depart from the experimentalism and become action art and more, in what may be called the expansion of art not art. The figure of the artist is revised throughout his multifaceted career; where, also, it can be underlined the writings for a theory of the (in) (not) art through creative work. Finally, it is mentioned some groups and artists who have accompanied or followed their proposals.